A Comparative Reading of John Keats’s Isabella and Lamia - Kul Bahadur Khadka, (Interdisciplinary Journal of Management and Social Sciences, 2022)
Keats’s Isabella and Lamia are narrative poems. They describe passionate love stories. In the former, two brothers with mercenary motive murder Lorenzo, the lover of their sister. Isabella, the sister, hides the cut-off head of the lover in a basil-pot. She loves the head. The cruel brothers steal the basil-pot with the head. Isabella pines and dies. The brothers are banished from Florence. In the latter, Lamia, a serpent-woman, seduces Lycius, a youth of Corinth. Apollonius, a sage or Lycius’s instructor, detects her identity and denounces her in their marriage feast. She vanishes. On the spur of moment, Lycius dies. This research article makes a comparative reading of Isabella and Lamia in terms of their sources, motifs, themes and characters. It has been structured into three parts- Introduction, Thematic patterns and Conclusion. John Keats’s respective poems and various books with critics’ opinions about Keats and his Isabella and Lamia have been consulted in course of preparing this research. The article concludes that Keats creates pleasure and horror in both poems mentioned above in order to balance two worlds- the real and the ideal.